Wind Energy Projection for the Philippines based on Climate Change Modeling - Silang, Angeli (Archīum Ateneo, 2014)
To complement the existing method of wind energy assessment, this study presents wind energy projection by downscaling a regional climate model, RegCM3, which is also used in predicting rainfall and temperature changes, and using a conversion method using the Weibull distribution. A couple of papers which used long-term predicting models focused on two regions, China and the US High Plains, show a decrease of about 14% and 7%-17% respectively in wind power density due to global warming over the next century. This paper focuses on a smaller grid size of 10 km x 10 km to concentrate on a specific wind farm in Pililla, Rizal, Philippines which is considered as a commercially feasible site by wind developers. Wind energy projection that considers the effects of climate change for the expected period of operation of 25 years is used because this gives wind developers an outlook on the power production during the wind farm's lifetime and would contribute in determining the wind farm's potential for financial returns. Percentage difference of wind power density between the baseline period of 2008-2012 and five-year projection periods from 2013-2037 are presented. Contrary to the results of studies in China and western US, the results of this research show that there is an average five-year period increase of 6% in wind power density in Pililla, Rizal over the next 25 years.